1985
DOI: 10.1073/pnas.82.9.3035
|View full text |Cite
|
Sign up to set email alerts
|

Intraterminal injection of synapsin I or calcium/calmodulin-dependent protein kinase II alters neurotransmitter release at the squid giant synapse.

Abstract: Synapsin I and calcium/calmodulin-dependent protein kinase II were pressure-injected into the preterminal digit of the squid giant synapse to test directly the possible regulation of neurotransmitter release by these substances. Neurotransmitter release was determined by measuring the amplitude, rate of rise, and latency of the postsynaptic potential generated in response to presynaptic depolarizing steps under voltage clamp conditions. Injection of dephosphosynapsin I decreased the amplitude and rate of rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
307
2
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 535 publications
(328 citation statements)
references
References 34 publications
18
307
2
1
Order By: Relevance
“…Synapsin I has been implicated in the regulation of neurotransmitter release in a variety of preparations (Llinas et al, 1985(Llinas et al, , 1991Lin et al, 1990;Lu et al, 1992;Pieribone et al, 1995). Numerous in vitro studies have shown that synapsin I acts to cross-link synaptic vesicles with actin filaments in a phosphorylation-dependent manner (B/ihler and Greengard, 1987;Petrucci and Morrow, 1987;Benfenati et al, 1993), a notion supported by electron microscopic observations of short bridging strands between synaptic vesicles and the cytoskeleton in nerve terminals (Landis et al, 1988;Hirokowa et al, 1989).…”
Section: Discussionmentioning
confidence: 67%
“…Synapsin I has been implicated in the regulation of neurotransmitter release in a variety of preparations (Llinas et al, 1985(Llinas et al, , 1991Lin et al, 1990;Lu et al, 1992;Pieribone et al, 1995). Numerous in vitro studies have shown that synapsin I acts to cross-link synaptic vesicles with actin filaments in a phosphorylation-dependent manner (B/ihler and Greengard, 1987;Petrucci and Morrow, 1987;Benfenati et al, 1993), a notion supported by electron microscopic observations of short bridging strands between synaptic vesicles and the cytoskeleton in nerve terminals (Landis et al, 1988;Hirokowa et al, 1989).…”
Section: Discussionmentioning
confidence: 67%
“…The activity of these kinases, especially the Ca 2 +-dependent kinase, may thus be a mechanism to modulate transmitter release. Indeed, a number of studies have shown that presynaptic stimulation, Ca2+-calmodulin kinase activity and synapsin phosphorylation correlate with the transmitter output (Nestler and Greengard, 1984;Llinas et al, 1985;Nichols et al, 1990). Both synapsin and the kinase may not be primary requirements for regulated exocytosis to function properly since mice lacking synapsin I or Ca: +-calmodulin kinase II both exhibit no overt phenotype and show normal synaptic transmission, but the absence of these proteins has clear effects on certain aspects of synaptic plasticity (Silva et al, 1992;Rosahl et al, 1993).…”
Section: The Availability Of Transmitters For Releasementioning
confidence: 99%
“…The Ca2+/calmodulin-independent form of CaM-kinase II was prepared by autophosphorylation, essentially as described (25). In brief, CaM-kinase II was incubated in a reaction mixture containing CaCl2 (0.5 mM), calmodulin (0.75 puM) and nonradioactive ATP (3 Proteolysis of CaM-Kinase II. CaM-kinase II was autophosphorylated for 5 min at 00C in standard kinase buffer containing 0.5 mM ATP (26).…”
Section: Methodsmentioning
confidence: 99%
“…In nerve terminals, CaM-kinase II catalyzes the phosphorylation of several proteins, including synapsin I, a protein associated with synaptic vesicles (2). Phosphorylation of synapsin I by CaM-kinase II is thought to participate in presynaptic modulation of neurotransmitter release (3).…”
mentioning
confidence: 99%